2016
DOI: 10.1108/mip-04-2015-0081
|View full text |Cite
|
Sign up to set email alerts
|

Market and innovation orientation typology: Proposition and illustrations

Abstract: Purpose The purpose of this paper is to develop a typology based on the market orientation (MO) and innovation orientation (IO) of firms, and to illustrate the extent to which public housing companies (PHCs) fit into this framework. Design/methodology/approach A qualitative study of 11 PHCs in central Sweden was conducted to classify their positions in the typology. Interviews with semi-structured and open-ended questions were used to colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…During recent decades, the impact of CSR on the effectiveness of MO has received significant interest in both practice and research [9]. Many companies invest heavily in implementing and integrating the CSR concept into different core activities [10,11], with the intention of improving their image and reputation [12] and/or to meet critical stakeholder demands on the market [13]. Plenty of studies have debated the CSR and business financial performance relationship [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…During recent decades, the impact of CSR on the effectiveness of MO has received significant interest in both practice and research [9]. Many companies invest heavily in implementing and integrating the CSR concept into different core activities [10,11], with the intention of improving their image and reputation [12] and/or to meet critical stakeholder demands on the market [13]. Plenty of studies have debated the CSR and business financial performance relationship [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Forceful companies are assumed to integrate MO into the organization as an intelligent mindset. This implies that a company's responsiveness to collected market information regarding consumer needs reflects the company's tendency, flexibility and ability to act successfully based on what the market wants and requires (Kohli and Jaworski, 1990; Sundström et al , 2016a; Hyder, 2016).…”
Section: Theoretical Discussion and Research Frameworkmentioning
confidence: 99%
“…Whereas innovation commonly refers to new products, services, production processes, organizational structure or administrative systems (Hult et al , 2004), innovativeness symbolizes an organization's entrepreneurial capabilities and cultural orientation toward the market (Liao et al , 2011). Sundström et al (2016a) noticed, however, that no obvious link between innovation and innovativeness exists. Companies can develop innovations driven by external expert demands without having developed the necessary internal capacity built on innovativeness.…”
Section: Theoretical Discussion and Research Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The category on understanding environmental dynamics is multifaceted and not only focusses on direct competition, but also on factors that can influence competition within a market place. It is therefore understandable that a range of studies found there to be a link between the ability of firms to manage market dynamism, competitiveness and innovation orientation (Manu, 1992;Stock and Zacharias, 2011;Prajogo and McDermott, 2014;Wu et al, 2015;Zhang et al, 2015;Sundström et al, 2016). Within this study, understanding environmental dynamics are based upon two key areas, technological dynamics and market dynamics, whereby technological dynamics are viewed as the rate and predictability of technological changes and market dynamics involve changes in customer preferences and market competition (Wu et al, 2015).…”
Section: Antecedents Of Innovation Orientationmentioning
confidence: 99%